The Slow Lingual Development in the Interlanguage Phase for Arabic Language Learners as a Second Language in Turkey - Abdulkader, Malek; Abdulkader, Malek (Aktif Yayınevi, 2024)
The study investigates the slow lingual development in the interlanguage phase for Ar abic language learners as a second language in Turkey. Furthermore, the study has three main pivotal questions: what are the characteristics of the transitional phase for Arabic language learners as a second language in Turkey?, What are the reasons for the slow lingual development in this phase for some learners? and what are the suggested solutions to solve this problem? The study uses the descriptive approach in addition to the error analysis approach as well. The study found that it is necessary to develop a specific strategy for knowledge-based feedback. Also, the study recommended the need for change and the diversification of teaching methods according to the teaching necessities in addition to the importance of lingual and cultural immersion for the Arabic language learner.
Yabancı Dil Öğretimi ve Disiplinlerarası Çalışmalar V. Uluslararası Dil Kongresi / Editörler:Doç. Dr. Mahmud Kaddum, Doç. Dr. Emad Abdelbaky Aly, Dr. Mohamed Ali Al-Dilj awii -- Aktif Yayınevi -- ISBN:978-625-8182-88-0 -- 2024.
Keywords: Teaching Arabic language for non-native speakers; Teaching Arabic language in Turkey; Interlanguage; Error analysis approach